Association Between Glycosylated Hemoglobin Level and Cardiovascular Outcomes in Diabetic Patients After Percutaneous Coronary Intervention. Issue 19 (May 2016) - Zheng, Jia; Cheng, Jing; Zhang, Qian; Qi, Cuijuan; Wang, Tong; Xiao, Xinhua
Abstract : Abstract: Glycosylated hemoglobin (HbA1c) is a critical measure of glycemic control, which may be a reliable predictor of complications after percutaneous coronary intervention (PCI). This systematic review and meta-analysis evaluates the association between HbA1c levels and clinical outcomes in diabetic patients after PCI. Pubmed, Embase, and Cochrane Library databases (dated to December 2015) were screened for relevant studies. Appropriate diabetic cases and controls, assessed using blood HbA1c levels, were extracted, and statistical analysis was conducted using RevMan 5.3 software. Summary odds ratios (ORs) with 95% confidence intervals (CIs) were used to calculate the associations between HbA1c levels and clinical outcomes in diabetic patients after PCI. Ethics review and approval was not necessary because this systematic meta-analysis did not involve any direct human trials or animal experiments. Eight studies that reported HbA1c levels for a total of 3290 diabetic subjects after PCI were included in this meta-analysis. Comprehensive integration and analysis revealed a significant correlation between higher HbA1c levels and the risk of target vessel revascularization progression (OR 1.36, 95% CI 1.03–1.82) and nonfatal myocardial infarction after PCI (OR 2.47, 95% CI 1.38–4.44). However, no significant association was found between HbA1c levels and major adverse cardiovascular events (OR 1.02, 95% CI 0.83–1.27), all-cause mortality (OR 0.73, 95% CI 0.52–1.02), cardiac death (OR 1.12, 95% CI 0.62–2.03), or in-stent thrombosis (OR 0.65, 95% CI 0.23–1.87) among diabetic patients after PCI. Sensitivity analysis indicated a statistically robust result and revealed no publication bias. Our meta-analysis demonstrated that blood HbA1c levels might be associated with higher risks of target vessel revascularization progression and nonfatal myocardial infarction among diabetic patients after PCI. However, further studies with larger sample sizes are required to verify the association. Abstract : Supplemental Digital Content is available in the text